2016
DOI: 10.1080/19476337.2016.1242157
|View full text |Cite
|
Sign up to set email alerts
|

Microbial and oxidation characteristics of refrigerated chicken patty incorporated with moringa (Moringa oleifera) leaf powder

Abstract: This study investigated the effect of different levels of Moringa oleifera leaf powder (MLP) on physicochemical, microbiological, and sensory characteristics of chicken patties during cold storage. For MLP extracts, methanolic extract exhibited flavonoid and total phenolic contents of 48.0 and 2010.3 mg/kg, respectively. The aqueous extract of MLP showed high (16.7 mm) and mild (8.7 mm) antimicrobial activity (inhibition zones) against Escherichia coli and Staphylococcus aureus, respectively. In chicken pattie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
16
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 35 publications
4
16
0
1
Order By: Relevance
“…Our findings also showed that over the storage period the pH of minced beef reduced significantly (P ≤ 0.05). Similar observations on pH reduction during storage of sausages formulated with moringa leaf powder or extract (Elhadi et al, 2017;Jayawardana et al, 2015) and microencapsulated Jabuticaba (Myrciaria cauliflora) extract (Baldin et al, 2016) have been reported.…”
Section: Ph and Peroxide Values Of Minced Beef Treated With Dlpe Durisupporting
confidence: 83%
See 4 more Smart Citations
“…Our findings also showed that over the storage period the pH of minced beef reduced significantly (P ≤ 0.05). Similar observations on pH reduction during storage of sausages formulated with moringa leaf powder or extract (Elhadi et al, 2017;Jayawardana et al, 2015) and microencapsulated Jabuticaba (Myrciaria cauliflora) extract (Baldin et al, 2016) have been reported.…”
Section: Ph and Peroxide Values Of Minced Beef Treated With Dlpe Durisupporting
confidence: 83%
“…Similarly, previous reports have shown that meat products formulated with moringa leaf and seed powder extracts exhibited higher pH values compared to unformulated controls Muthukumar, Naveena, Vaithiyanathan, Sen, & Sureshkumar, 2014;Shah, Bosco, & Mir, 2015). Contrasting reports have indicated that incorporation of moringa leaf powder or extract in chicken sausages significantly reduced the pH of the product (Elhadi et al, 2017;Jayawardana et al, 2015). The divergent results obtained from these studies might be due to differences in materials and extracts used.…”
Section: Ph and Peroxide Values Of Minced Beef Treated With Dlpe Durimentioning
confidence: 75%
See 3 more Smart Citations